Signaling pathways of marine-derived natural products on lung injury: from the in vivo perspective - Wang, Haitong; Qiu, Feng (Frontiers in Pharmacology, 2026)
Lung injury is characterized by impaired gas exchange, inflammatory responses, and abnormal tissue repair. In severe cases, it can progress to respiratory failure, posing a threat to public health. Marine natural products, due to their structural and biological activity diversity, show significant potential in the treatment of lung injury. This article systematically reviews the mechanism by which marine-derived natural products improve lung injury by regulating key signaling pathways in vivo. Studies have demonstrated that marine natural products target pathological processes such as inflammatory immunity and oxidative stress by regulating signaling pathways including αvβ3-FAK/Src, TLR4/MyD88, NF-κB, and Keap1-Nrf2/HO-1/STAT3, thereby exerting a significant protective effect on alveolar structures in lung injury models induced by stimuli such as radiation, OVA, LPS, and cigarette smoke. Currently, there is a lack of marine drugs specifically for lung injury, and in-depth research is needed to promote their translation into clinical medications.